TINJAUAN HUKUM ISLAM TERHADAP AKAD SALAM DENGAN SISTEM ONLINE DI ONLINE SHOP INDRA CMP ASEMBAGUS SITUBONDO - Jonwari; Faiz Zainuddin (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
This paper is the result of field research on "Review of Islamic Law on Salam Contracts with Online Systems at the Indra CMP Asembagus Situbondo Online Shop", this study aims to answer questions about:, How is the implementation of salam contracts with online systems at Indra CMP Asembagus online shop Situbondo Asembagus Situbondo. and, How is the Islamic law review of the salam contract with the online system at Indra CMP Asembagus Situbondo's online shop. This study uses a qualitative method. The results of the study conclude that the relationship of the parties in the salam contract agreement with the online system is the same as the usual salam contract agreement. However, the sale and purchase of salam contracts with an online system does not meet directly between buyers and sellers, it's just that the perpetrators of the contract are brought together in one internet network site. In Islamic law, a sale and purchase contract is allowed to enter into a contract using writing (letters) on the condition that the two parties are far apart from each other or the contract actors are silent, for the perfection of the contract it is required that the other person addressed by the writing is willing to read the writing. A review of Islamic law on salam contracts with an online system can be concluded that online salam contracts are allowed as long as they do not contain elements that can damage them such as usury, injustice, fraud, fraud and the like and fulfill the pillars and conditions in buying and selling.